Uso de los Recursos Educativos Digitales sobre Ciudadanía Digital del portal web del Ministerio de Educación del Ecuador por parte de los docentes del nivel de Bachillerato General Unificado en la Unidad Educativa Fiscomisional Daniel Álvarez Burneo en el año lectivo 2023-2024. - Mendoza GuamánMendoza, Anderson Elian (2024)
Currently, the use of Digital Educational Resources (DER) has become essential in the teaching-learning process, enhancing teachers' pedagogical practices and fostering meaningful learning experiences for students. This curricular integration project analyzes the use of DER on Digital Citizenship from the Ecuadorian Ministry of Education's web portal by Unified General Baccalaureate teachers at the “Unidad Educativa Fiscomisional Daniel Álvarez Burneo” during the 2023-2024 academic year. Employing a deductive methodology with a quantitative, exploratory-descriptive approach and non-experimental design, the study surveyed 20 teachers involved in Digital Citizenship instruction. A specifically developed data collection instrument was administered via survey, and results were organized using frequency tables and illustrated through bar and pie charts for clarity. The analysis identified 10 DERs for Digital Citizenship, categorized into three thematic areas: digital environment issues prevention, social relationships, and online safety. Within these categories, key resources included Talking about Everything a Little (prevention), Expressions (social relationships), and A New Community (safety). Findings reveal that teachers use all DERs provided on the Ministry of Education’s web portal, though the frequency of usage differs across resources. Keywords: Digital Educational Resources, Digital Citizenship, Ministry of Education of Ecuador, Unified General Baccalaureate.